Types and Functions of Code-Switching in English Learning Contexts: Insights from SMK Bahari Parepare - Nildasari; Nur, Rafiah; Latifa, Ammang (ETERNAL (English, Teaching, Learning and Research Journal), 2024)
This study explores the types of code-switching used by English teachers and students at SMK Bahari Parepare, aiming to know the function of code switching in learning proses. This research was conducted in SMK Bahari Parepare, by employing qualitative research methods. The sample in this study is one English teacher and 12 students in eighth grade nursing department in the 2023/2024 academic year. Next, process collecting data used observation checklist and note taking observation and also used the form of conversation recordings were then transcribed and analysed descriptively qualitatively using thematic analysis. The research identifies three primary types of code-switching: tag switching, inter-sentential switching, and intra-sentential switching. Tag switching was found to be a common strategy among students, often used to clarify understanding or manage classroom dynamics. In contrast, inter-sentential switching served as a bridge between languages, allowing for clearer communication of instructions and concepts, while intra-sentential switching facilitated the expression of complex ideas within a single utterance. Overall, the study concludes that code-switching significantly contributes to the effectiveness of English language instruction at SMK Bahari Parepare. It enables students to connect new language concepts with their native language, fostering a more inclusive and supportive learning environment. The research underscores the importance of recognizing and integrating code-switching in educational practices, as it enhances both understanding and language proficiency among students, ultimately promoting their confidence in using English.